More than 50% reduction of wear in polyethylene liners with alumina heads compared to cobalt-chrome heads in hip replacements: A 10-year follow-up with radiostereometry in 43 hips - Dahl, Jon (Informa Healthcare, 2013)
BACKGROUND AND PURPOSE: Excessive wear of acetabular liners in hip replacements may lead to osteolysis and cup loosening. Different head materials are currently used. We measured differences in wear between alumina and cobalt-chrome heads with the same polyethylene liner. PATIENTS AND METHODS: 39 patients (43 hips) with osteoarthritis were included in a study with 10-year follow-up. Wear was measured as proximal and 3D penetration of the head in the liner with radiostereometry (RSA). All the patients were followed clinically with Harris hip score (HHS) for up to 10 years. Radiolucent lines and osteolytic lesions were assessed on plain radiographs. RESULTS: With alumina heads, proximal wear (95% CI) after 10 years was 0.62 (0.44–0.80) mm as compared to 1.40 (1.00–1.80) mm in the cobalt-chrome group. For 3D wear, the results were 0.87 (0.69–1.04) mm for alumina heads and 1.78 (1.35–2.21) mm for cobalt-chrome heads. Median (range) HHS was 98 (77–100) in the alumina group and it was 93 (50–100) in the cobalt-chrome group (p = 0.01). We found no difference in osteolysis between the groups. INTERPRETATION: We found better wear properties with alumina heads than with cobalt-chrome heads. We recommend the use of alumina heads in patients in whom a high wear rate might be anticipated.